"Ciwewe". Culture and Power in a "cokwe" song from the East of colonial Angola, 1955 - Sá Valentim, Cristina (Revista de Antropología Social, 2016)
This article analyzes the political potential of culture and subjectivity from one of several cokwe songs collected by a diamonds enterprise named Diamang in the Northeast of Angola during Portuguese colonial rule. Drawing from ethnographic data from Angolan oral history and Portuguese colonial archives, and taking into account post-colonial perspectives and contemporary anthropological studies, I would like to reflect about the relation between power, culture and subjectivity in contexts of colonial oppression and subalternity. I suggest that the analysis on music (and on related cultural expressions as dance, song and poetry) performed in the rural settings in Angola during the colonial rule, and on the subjectivity around and from it, is crucial to understand a distinctive practice of a culture and history and, at the same time, the Angolan engagements within new colonial realities which occurred through ambiguous and complex logics made by interwoven dynamics of control and resistance.